2003
DOI: 10.1007/s11745-003-1119-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of struture and form on the ability of plant sterols to inhibit cholesterol absorption in hamsters

Abstract: We investigated the effect of three types of plant sterols (4-desmethylsterols, 4,4′-dimethylsterols, and pentacyclic triterpene alcohols) in three forms (free, esterified with FA, or with phenolic acids) on cholesterol absorption. Plant sterol fractions derived from soybean (99% 4-desmethylsterols), rice bran (70% 4,4′-dimethylsterols), or shea nut (89% pentacyclic triterpene alcohols) were fed to male hamsters (n = 20/group) as free sterols or esterified with FA or phenolic acids (cinnamic or ferulic). Chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
3
24
2
Order By: Relevance
“…Richelle et al showed that when unesterified or esterified plant sterols were given to normocholesterolemic humans, the inhibitory effect on cholesterol absorption was similar between these two preparations ( 10 ). A similar observation was also reported in hamsters ( 11 ). The results suggest that the effect of these two forms can be comparable in humans and hamsters.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Richelle et al showed that when unesterified or esterified plant sterols were given to normocholesterolemic humans, the inhibitory effect on cholesterol absorption was similar between these two preparations ( 10 ). A similar observation was also reported in hamsters ( 11 ). The results suggest that the effect of these two forms can be comparable in humans and hamsters.…”
Section: Discussionsupporting
confidence: 89%
“…Plant sterol stearates contained more stigmasterol and less ␤ -sitosterol and ␤ -sitostanol compared with unesterified plant sterols and plant sterol oleates. [4][5][6][7][8][9][10][11][12][13][14] C] cholesterol (55 mCi/mmol) was purchased from Amersham Pharmacia Biotech, Tokyo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no other studies have shown the effects of plant sterol or stanol analogues in reducing absorption of energy substrates. Both humans 3 and hamsters [15][16][17] absorb approximately 50% of dietary cholesterol in the intestinal tract. It is known that DAPP, as well as traditional plant sterols, inhibit intestinal cholesterol absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Results of different studies, testing whether sterol/ stanol mixtures influence each others absorption or excretion or metabolic effects are not conclusive (Normén et al, 2000;Nestel et al, 2001;Naumann et al, 2003). Studies with sterols from less common sources such as sheanut oil or ricebran oil show conflicting results (Weststrate and Meijer, 1998;Sierksma et al, 1999;Vissers et al, 2000;Meijer et al, 2003). Non-hydrogenated tall oil sterols or stanols in their fatty acid esterified form are not used in the food supply nor have they been studied, so it is important to demonstrate the cholesterol-lowering ability of this novel source.…”
Section: European Journal Of Clinical Nutrition (2008) 62 968-977mentioning
confidence: 99%